Decreased athlete motor skills: before and after activity coronavirus disease (COVID-19) pandemic - Pardilla, H.; Henjilito, R.; Asilestari, P.; Husnayad, I. (Indonesian Sport Innovation Review, 2021)
The purpose of the study. is study was to look at the impact of pandemic 19 before and after Activity Coronavirus disease (B-A COVID-19P) on the performance of athletes' motor skills (MS) Materials and methods. The participants (Sample / N = 40) are national athletes in the Field Jumping category (Triple jump, Long jump and High jump), Riau Province of Indonesia, aged 18-20 years. The test instrument in determining the level of MS in athletes is the Motor Ability Test (7 item test) Results. The results of the Paired Sample test B-A COVID-19P have sig values. ie 0.00 If seen with a significance standard of 0.05 or 5%, p-values of 0.000 <0.05 and H1 are accepted. This means that there are significant differences between motor skills in B-A COVID-19P. Conclusions. With the conclusion that MS in track and field athletes there is a decrease in performance after the impact of the Covid-19 pandemic.